The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2166/h2oj.2022.137
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to address unsafe child feces disposal practices in the Asia-Pacific region: a systematic review

Abstract: Despite clear evidence of the adverse health impacts of unsafe child feces disposal (CFD), there is little evidence of the effectiveness of interventions targeting the improvement of unsafe CFD practices in this region. A systematic review of the literature was conducted to identify and evaluate the quality of both behavior change and hardware interventions targeting the improvement of CFD practices in the Asia-Pacific region. A total of 695 articles were screened, and 11 studies were included. The combined ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Even so, open disposal was still common in homes with toilets. According to a systematic review conducted in the Asia-Pacific area, these results point to the importance of putting large-scale programs and hardware interventions into place in order to give communities the tools they need to modify their habits and behaviors in the presence of improved latrine [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even so, open disposal was still common in homes with toilets. According to a systematic review conducted in the Asia-Pacific area, these results point to the importance of putting large-scale programs and hardware interventions into place in order to give communities the tools they need to modify their habits and behaviors in the presence of improved latrine [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this review, PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines (Moher et al, 2009;Sprouse et al, 2022) were followed to identify all the relevant publications pertaining to FS emptying in Sub-Saharan Africa (SSA), South Asia and Southeast Asia. These regions were chosen because of their wide coverage with OSS and in turn widely spread emptying businesses (Tremolet, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Open defecation (OD) refers to the practice of defecating or disposing of human feces in fields, forests, bushes, bodies of water, or other open spaces (WHO and UNICEF, 2021). Given its linkages to human health, dignity, and gender equity, eliminating OD has remained a global goal and water, sanitation, and hygiene (WASH) sector priority (Beardsley et al, 2021;Sprouse et al, 2022) manifesting in an international agreement on the human right to water and sanitation and the United Nations SDG 6.2 to achieve by 2030 access to adequate and equitable sanitation and hygiene for all and end OD (United Nations, 2022). Between 2000 and 2020, the World Health Organization/United Nations Children's Fund Joint Monitoring Programme (JMP) reported that the proportion of the global population practicing OD decreased from 21% to 6%; however, an estimated 494 million people still practice OD, of whom 90% live in rural areas of sub-Saharan Africa and Central and Southern Asia (WHO and UNICEF, 2021).…”
Section: Introductionmentioning
confidence: 99%